PENINGKATAN KUALITAS PELAYANAN AKTA KELAHIRAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BATANG - Hanitasari Susilowati; Hartuti Purnaweni; Nina Widowati (Journal of Public Policy and Management Review, 2014)
The back ground of this research caused several complains about the less ofbirth certificate service and less of the ownership birth certificate in epartment of population and civil registration Batang. Actually each a birth must be reported depend on the UU number 23 2006 about administration inhabitant. In this research the researcher used descriptive qualitative method. The location of this research focused in department of population and civil registration Batang. The sampling of this research used purposive sampling. To analyze the data qualification the researcher used triangulasi technique. Phenomenon that influences the service quality of birth certificate measured from the dimensions of service quality according Zeithaml, Parasuraman, and Berry in applying diminutions of tangible, responsiveness, reliability, assurance, and empathy (Tjiptono: 2011). Meanwhile, the improvement of service quality according to State Administration Intuition measuring from the leadership factor, empowerment of employees and the change management.Service quality of birth certificate in department of population and civil registration Batang didn’t well caused the dimensions of tangible, responsive and reliability didn’t applied optimally. The improvement efforts of population and civil registration department still have some problems, there are; less of commitment of the employees, less of the inhabitant participation in completing the data of population administration.There are some recommendations that provided (1) creates an strongorganization image, consistent, and responsive to changes and cares about the environment; (2) conducts staffing training about discipline work to all of the employees; (3) enhancing the environment security systems and data security services; (4) the leader give motivation and attention to the employees; (5) building the system of reward and punishment; and (6) Conducted the socialization about the importance of the administrative completeness of population.